2018
DOI: 10.1002/tox.22636
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of Rutin on sodium fluoride‐induced hypertension through modulation of Kim‐1/NF‐κB/Nrf2 signaling pathway in rats

Abstract: Sodium fluoride is one of the neglected environmental contaminants. Inorganic fluorides in the environment are found in the air, water, and land. In the study, forty‐male Wistar albino rats were randomly divided into four groups with 10 rats in a group. Group A was the control group which was given normal saline, Group B was exposed to 300 ppm of NaF in drinking water, while Groups C and D received NaF along Rutin (100 mg/kg and 200 mg/kg) orally daily for a week. Administration of NaF alone led to significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Rutin is a flavonol that presents in buckwheat and citrus fruits. In a sodium fluoride-induced hypertensive rats, administration of rutin reduced blood pressure elevation by enhancing NO bioavailability via down-regulation of NFκB expression and up-regulation of Nrf2 (Oyagbemi et al, 2018b).…”
Section: Anti-inflammatory Effects Of Flavonoids In Cvds Via Modulatimentioning
confidence: 99%
“…Rutin is a flavonol that presents in buckwheat and citrus fruits. In a sodium fluoride-induced hypertensive rats, administration of rutin reduced blood pressure elevation by enhancing NO bioavailability via down-regulation of NFκB expression and up-regulation of Nrf2 (Oyagbemi et al, 2018b).…”
Section: Anti-inflammatory Effects Of Flavonoids In Cvds Via Modulatimentioning
confidence: 99%
“…Again, several human studies have found that exposure to excessive F is closely associated with hypertension [546,547,548,549,550]. Similar observations have been observed in experimental studies with rodents [551,552,553,554,555,556]. Interestingly, activation of the TRH system, with increased production of TRH and an upregulation of its receptors has also been implicated in the pathogenesis of hypertension [557].…”
Section: Discussionmentioning
confidence: 64%
“…Increasing evidence also suggests that maternal iodine deficiency and hypothyroidism is associated with increased risk of cognitive impairment, neurodevelopmental and neuropsychiatric disorders in offspring including ADHD [511,512,513,514,515,516,517,518,519,520,521,522,523,524,525,526,527,528,529,530,531,532,533,534,535,536,537,538,539,540,541,542,543,544,545,546,547,548,549,550,551,552,553,554,555,556,557,558,559,560,561,562,563,564,565], ASD [566,567,568], behavioural seizures [517] and schizophrenia [516]. Moreover, maternal iodine deficiency and hypothyroidism is also associated with increased risk of asthma [518] and hypertension [569] in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training can relieve hypertension by targeting NF-κB signaling in the hypothalamic paraventricular nucleus ( 31 ). Rutin has been reported to ameliorate sodium fluoride-induced hypertension by regulating NF-κB/Nrf2 signaling in rats ( 32 ). The present study revealed that the phosphorylation of ERK, p65 and IκBα was stimulated by Ang II, and sinigrin treatment reduced this effect in a concentration-dependent manner in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%